Organizational Conflict Management In Creating Effective Communication of Higher Education Employees (Case Study at Darul ‘Ulum University Jombang) - Alip Sugianto; Veri Setiawan (BPSDMP Kominfo Manado, 2020)
The purpose of this research is to explain how promotes management conflict and communication effective. This kind of conflict can happen to everyone and in any places disregarding status, income and position. Someone who cannot manage conflicts will have a threat for his personal performance, and unfortunately, company’s performance will also gain the effect. Accordingly, we need a strategy to manage conflicts as an effort to create a good performance for individual employee performance as well as the team performance. Communication means providing information and distributing to the members of the organization, if the distribution is hampered because of the bad behavior committed by a person or one of the employees of the communication that exists becomes ineffective. In the long term ineffective communications will result in the emergence of misunderstanding interpretation giving rise to prejudice and ultimately lead to internal conflicts within the company or organization. Role management is urgently needed to resolve the conflict because of the impact of impact of the conflict will impact on the performance and effectiveness of the work in the company especially in in Darul Ulum University. Key words: conflict management, effective communication, organization.